Engineered Domain Swapping as an On/Off Switch for Protein Function - Ha, Jeung-Hoi (Chem Biol, 2015)
Domain swapping occurs when identical proteins exchange segments in reciprocal fashion. Natural swapping mechanisms remain poorly understood and engineered swapping has the potential for creating self-assembling biomaterials that encode for emergent functions. We demonstrate that induced swapping can be used to regulate function of a target protein. Swapping is triggered by inserting a ‘lever’ protein (ubiquitin) into one of four loops of the ribose binding protein (RBP) target. The lever splits the target, forcing RBP to refold in trans to generate swapped oligomers. Identical RBP-ubiquitin fusions form homo-swapped complexes with the ubiquitin domain acting as the hinge. Surprisingly, some pairs of non-identical fusions swap more efficiently with each other than they do with themselves. NMR experiments reveal that the hinge of these hetero-swapped complexes maps to a region of RBP distant from both ubiquitins. This design is expected to be applicable to other proteins to convert them into functional switches.